Is It Because You Don’t Want to? A Content Analysis of Police Executive Leaders’ Perceptions of Policewomen’s Careers in Europe - Antón Rubio, Concha; Grueso Hinestroza, Merlin Patricia; Marín López, Montserrat (Frontiers in Psychology, 2021)
The impediments and barriers that women face in entering and developing a police career have received relatively little attention from researchers. In Europe today, despite the slow progress, the 25% barrier to female representation has already been overcome in several countries. However, many areas remain closed to women within police organizations. In this context, research was conducted based on a content analysis of the perceptions of 56 police officers, 28 men and 28 women with considerable police experience, occupying executive leadership positions, from a total of 26 European countries. Data was collected through a questionnaire composed of 23 open questions. The results show the enormous gap between the perceptions of male and female police executive leaders with regard to access, career development and workplace conditions faced by police women and men. According to the results, the mirage of equality, dominant in the view of male police officers, is a major barrier to achieving real equality, both horizontally and vertically. What implications these results have on the strategies that police organizations should follow in order to achieve the challenge of inclusion are discussed and new ways of analysis are proposed.